The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/medicina59010073
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Curve of Surgery of Diabetic Tractional Retinal Detachment—A Retrospective, Comparative Study

Abstract: Background and Objectives: There are few data in the literature concerning the learning curve of tractional retinal detachment (TRD) surgery. We have analyzed the experience gained by a vitreoretinal surgeon over 10 years. Materials and Methods: A retrospective, comparative study of 34 TRD cases operated using 20G instruments between 2008 and 2011 (group A) and 94 cases operated using 23G instruments between 2015 and 2019 (group B). The preoperative characteristics, the type of endotamponade, and the anatomica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In our research, the flicker response was delayed in subjects with PDR, a fact that is in agreement with other studies that report an increased implicit time in diabetics with advanced stages of DR [34][35][36][37][38] and are normal or minimally affected in early stages [39][40][41][42][43].…”
Section: Discussionsupporting
confidence: 93%
“…In our research, the flicker response was delayed in subjects with PDR, a fact that is in agreement with other studies that report an increased implicit time in diabetics with advanced stages of DR [34][35][36][37][38] and are normal or minimally affected in early stages [39][40][41][42][43].…”
Section: Discussionsupporting
confidence: 93%
“…Diabetic retinopathy (DR) is the most common microvascular complication of T1D and one of the leading causes of irreversible blindness even in developed countries [7,8]. The prevalence of DR among diabetic patients is 34.6% worldwide, meaning approximately 93 million people are diagnosed with diabetic retinopathy, 21 million of them with diabetic macular edema and 17 million with proliferative diabetic retinopathy [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the majority of studies included in the present review, secondary FAS rates were greater than primary SSAS rates [ 41 88 ]. One study suggested that tailoring treatment to the specific needs of each patient can help surgeons optimize anatomic success rates and improve anatomical outcomes in patients with retinal detachment [ 89 ].…”
Section: Discussionmentioning
confidence: 99%